A Lagrangian Perspective of Microphysical Impact on Ice Cloud Evolution and Radiative Heating. (31st October 2022) - Sullivan, S.; Voigt, A.; Miltenberger, A.; Rolf, C.; Krämer, M.
Abstract: We generate trajectories in storm‐resolving simulations in order to quantify the effect of ice microphysics on tropical upper‐tropospheric cloud‐radiative heating. The pressure and flow field tracked along the trajectories are used to run different ice microphysical schemes, both one‐ and two‐moment formulations within the Icosahedral Non‐hydrostatic Model model and a separate offline box microphysics model (CLaMS‐Ice). This computational approach allows us to isolate purely microphysical differences in a variant of "microphysical piggybacking;" feedbacks of microphysics onto pressure and the flow field, for example, via latent heating, are suppressed. Despite these constraints, we find about a 5‐fold difference in median cloud ice mass mixing ratios ( q i ) and ice crystal number ( N i ) between the microphysical schemes and very distinct q i distributions versus temperature and relative humidity with respect to ice along the trajectories. After investigating microphysical formulations for nucleation, depositional growth, and sedimentation, we propose three cirrus lifecycles: a weak source‐strong sink lifecycle whose longwave and shortwave heating are smallest due to short lifetime and low optical depth, a strong source‐weak sink lifecycle whose longwave and shortwave heating are largest due to long lifetime and high optical depth, and a strong source‐strong sink lifecycle with intermediate radiative properties. Plain Language Summary: The number and mass of ice crystals in upper‐level clouds affect how much infrared radiation these clouds absorb and how much sunlight they reflect. Changing the description of how these crystals form and grow in models directly alters the crystal number and mass. But it can also indirectly alter the number and mass by changing temperature or available moisture via, for example, latent heating. We control for these indirect changes by using the same set of variables to run different models of ice crystal formation and growth. Even with the indirect changes suppressed, we produce a large variation in the number and mass of ice crystals with different models. We dig into why this is by looking at parameters describing crystal formation, growth, and sedimentation. The strength of these three processes generates distinct ice cloud lifecycles for which infrared radiation and sunlight are also absorbed and reflected with differing strength. Key Points: Even with feedbacks constrained, ice mass varies 5‐fold with structural differences in cirrus microphysics These differences develop rapidly within trajectory lifetime due to differences in representations of ice nucleation Three cirrus lifecycles with distinct radiative signatures are proposed